Pengaruh Volume Perdagangan, Nilai Tukar Rupiah, BI Rate, Inflasi Terhadap Harga Saham Perusahaan Farmasi yang Terdaftar di BEI Selama Covid-19 (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of stock trading volume, exchange rates, BI rates and inflasi on stock prices in pharmacy companies listed on the BEI during the pandemic. The object studied in this study are 9 pharmacy companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This type of research is quantitative research. The population in this study is the pharmacy of companies listed on the Indonesia Stock Exchange for the period 2020-2022. The research sample was selected using purposive sampling. This study uses secondary data obtained through the website of the Indonesia Stock Exchange and Bank Indonesia. The data analysis technique in this research is panel data regression analysis. The results showed that the variables of exchange rate, BI Rate had no effect on stock prices, while the inflation and stock trading volume variables had an effect on stock prices.